Minimalist syntax : exploring the structure of English - Radford, Andrew (Cambridge : Cambridge University Press, 2004)
Andrew Radford's textbook, Minimalist Syntax, provides a concise, clear, and accessible introduction to syntactic theory, drawing on the key concepts of Chomsky's Minimalist Program. Assuming little or no prior knowledge of syntactic theory, Radford takes students through a diverse range of topics in English syntax - such as categories and features, merger, null constituents, movement, case, and split projections - and shows how the'computational component' works within the minimalist framework. Beginning at an elementary level, the book introduces grammatical concepts and sets out the theoretical foundations of Principles and Parameters and Universal Grammar, before progressing in stages towards more complex phenomena. Each chapter contains a workbook section, in which students are encouraged to make their own analyses of English phrases and sentences through exercises, model answers, and'helpful hints'. There is also an extensive glossary of terms.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: English language -- Syntax; Grammar, Comparative and general -- Syntax